2015
DOI: 10.26740/jpi.v1n1.p96-104
|View full text |Cite
|
Sign up to set email alerts
|

Proses Fonologis Dalam Pengadopsian Kata Bahasa Indonesia Ke Dalam Bahasa Cia Cia Di Kabupaten Buton, Sulawesi Tenggara

Abstract: This paper discusses the adoption of several phonological processes in Indonesian words into Ciacia in Buton, Southeast Sulawesi province. Ciacia language which is one of the languages with the most speakers in mainland Buton Kingdom in its development are adopting some Indonesian words. Adoption of words in Indonesian as compared to most other areas of the language word. This is due to ethnic mixing Ciacia just used both languages in daily life. In adopting Indonesian words into Ciacia many who have phonologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Aside from research about borrowing words in Javanese, there is also other research which discussed phonological process using generative phonology in different language. There also some of researchers (Putu, Nyoman Seri, & Suparwa, 2015;Obied, 2015;Indrawati 2015;Sutarsih, 2017;Salem Alqahtani, 2018;Al-Hindawi & Al-Aadili, 2018) which have studied a phonological process of other language instead of Javanese using generative phonology theory. Although all of the studies have used the same theory as the writer used in this journal, but they did not created the rules of processes using distinctive features.…”
Section: Introductionmentioning
confidence: 99%
“…Aside from research about borrowing words in Javanese, there is also other research which discussed phonological process using generative phonology in different language. There also some of researchers (Putu, Nyoman Seri, & Suparwa, 2015;Obied, 2015;Indrawati 2015;Sutarsih, 2017;Salem Alqahtani, 2018;Al-Hindawi & Al-Aadili, 2018) which have studied a phonological process of other language instead of Javanese using generative phonology theory. Although all of the studies have used the same theory as the writer used in this journal, but they did not created the rules of processes using distinctive features.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the analysis were in line with Lapoliwa's (2006) study which reported that several phonological changes occurred in Indonesian in terms of degemination of consonants, deletion of trill, deletion phoneme of /h/, reduction of syllables, naturalization phonemes of /z/, /x/, deletion of schwa, nasalization of vowels, insertion of sounds, and sliding of 'glide insertion'. Indrawati (2015) reported that the addition and deletion of sounds at the end of words and the words adopted into Ciacia language, in Buton district, Southeast Sulawesi always have several open syllables. This is because the Ciacia language does not have closed syllables.…”
Section: The Differences Of Phonological Change Forms Between Englishmentioning
confidence: 99%
“…Francis and Taylor discuss how the types of prefix negation go through their morphological or word formation. Meanwhile, Indrawati (2015) conducted a study on the Phonological Process in Adopting Indonesian Words into Ciacia in Buton District, Southeast Sulawesi and found the phonological processes that occur in the adoption of Indonesian words into Ciacia in the form of adding and removing sounds at the end of words. That is because the Ciacia language does not recognize the existence of words with closed tribes.…”
mentioning
confidence: 99%